Clube de leitura Tertúlias do Grão Pará na pandemia: uma vivência na EMEF Novo Tauari - TEIXEIRA, Débora Thaissa Monteiro (2024)
This work presents the process of implementing a reading club during the pandemic period, as a space for training readers, in view of the legitimate encounter between the reader and the reading of children's literature in a municipal school in Ananindeua-PA. The aim was to promote the democratization of children's literature books and train literary readers. The project was developed based on studies on the origin of the reader and the reader community, developed by Lucio (2017). Following the perspective of the training research methodology, under the guidance of studies by Bortolin (2014); Candido (2011); Compagnon (2009); Curia (2012); Freitas (2007); Lucio (2017) and Santos (2014). Allying with the contributions of the discursive perspective discussed by Smolka (2012), also seeking to systematize actions that allow the fruition of the literary text discussed by Abramovich (1997), who acts directly in the literacy processes. The analysis of the results allows us to conclude that, despite the challenges, the actions of the reading club provided the training of those responsible and the children - who had no reading heritage, helping in the insertion of written culture and literacy.